2021
DOI: 10.21203/rs.3.rs-275591/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A large-scale multi-ethnic genome-wide association study of coronary artery disease

Abstract: Coronary artery disease (CAD) is a leading cause of death, yet its genetic determinants are not fully elucidated. We report a multi-ethnic genome-wide association study of CAD involving nearly a quarter of a million cases, incorporating the largest cohorts to date of Whites, Blacks, and Hispanics from the Million Veteran Program with existing studies including CARDIoGRAMplusC4D, UK Biobank, and Biobank Japan. We verify substantial and nearly equivalent heritability of CAD across multiple ancestral groups, disc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…This shortcoming remains a barrier to more broadly studying polygenic risk for CAD in diverse populations. With recent efforts to improve representation in CAD GWAS, 7 we hope that future PRS research will expand to address this limitation. A second limitation of this work is that our methods do not allow for causal inference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shortcoming remains a barrier to more broadly studying polygenic risk for CAD in diverse populations. With recent efforts to improve representation in CAD GWAS, 7 we hope that future PRS research will expand to address this limitation. A second limitation of this work is that our methods do not allow for causal inference.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to assessing the impact of polygenic risk for CAD has been to measure associations between a CAD PRS and biobank-derived phenotypes. 6,7 A primary advantage of this approach is the large number of participants in such biobanks. However, a limitation of this method is lack of precision for some outcomes, particularly those inferred from electronic health records.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, PCSK9 is a well-documented drug target, not only for lipids but also for cardiovascular events 58-60 . In comparison to published studies 61 , others find a non-significant increased risk for T2D 62 and an arguably stronger protective effect for CAD 63 , for PCSK9 variant carriers. Our observation is consistent with the lack of excess T2D risk observed in PCSK9 inhibitor clinical trials 58-60,64 and with strong protective effects for coronary heart disease 65 .…”
Section: Discussionmentioning
confidence: 59%
“…The GWAS meta-analysis results of CAD and T2D were acquired from MVP 63 and DIAGRAM Consortium 62 , respectively. For variant rs1229984, the CAD result is from CARDIoGRAM Plus C4D meta-analysis 99 , as it was not present in the MVP results.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified a large number of genetic loci associated with coronary heart disease 42 44 , ASCVD 45 - 47 , HF 48 , 49 , and their risk factors, such as BMI 50 , 51 , blood lipids 52 , 53 , blood pressure 54 57 , and T2DM 58 ; however, these genetic variations explain only a small portion of risk in populations 59 , 60 . Joint genetic-environmental effects may be a key mechanism responsible for unexplained CVD risk.…”
Section: Genetic Basis Of Atherosclerotic Cardiovascular Disease and Heart Failurementioning
confidence: 99%